APAKAH SHOPPING EMOTION DALAM MEMEDIASI PENGARUH PROMOSI PENJUALAN MENINGKATKAN IMPULSE BUYING? - Rofiah, Chusnul; Rohmah , Asya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine and explain the significant effect of sales promotion on impulse buying with shopping emotion as an intermediary variable (study on marketplace users). The research uses an explanatory research method which is carried out through data collection in the field. The population is Jombang students with a sample of 100 respondents. Data analysis uses simple linear regression statistical 4 models methods, hypothesis testing and coefficient of determination. Based on the results of data analysis and discussions that have been carried out, it can be concluded that sales promotion has a good contribution in influencing shopping emotion, so that the higher sales promotion, the higher shopping emotion of shopee marketplace consumers. Shopping emotion has a good contribution in influencing impulse buying, so the better the emotional shopping, the higher the impulse buying of consumers who use the shopee marketplace.